Emodin weakens liver inflammatory injury triggered by lipopolysaccharide through elevating microRNA-145 in vitro and in vivo - RuiJin Xie; Mei Liu; ShuJie Li (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Hepatitis is a severe liver disease with worldwide distribution. This study explored the anti-inflammatory influence of Emodin on LPS-triggered liver injury in vitro and in vivo. In vitro, we discovered that LPS treatment triggered L-02 cell and primary hepatocyte inflammatory injury. Emodin weakened the LPS-triggered cell inflammatory injury and NF-κB pathway activation. Emodin alleviated LPS-stimulated decrease of miR-145 expression. Moreover, miR-145 participated in the regulation of pro-inflammatory factors expression and negatively regulated IRAK1. Besides, IRAK1 exert regulatory roles in the activation of NF-κB pathway. In vivo, we found that Emodin pre-treatment weakened the LPS-triggered increases of pro-inflammatory factors expression, up-regulations of AST and ALT level, liver cell apoptosis, reduction of miR-145 and enhancement of IRAK1. Our research verified that Emodin weakened LPS-triggered liver cell inflammatory injury in vitro and in vivo might be achieved by elevating miR-145, decreasing IRAK1 and then suppressing NF-κB pathway.